Diseño de un economizador para una caldera de 500BHP (2018)
Initially, the characterization of the gases produced by the combustion in the boiler was carried out, giving way to the parameterization of the design. Subsequently, a temperature analysis of the gas outlet vs the exit temperature of the water from the economizer was carried out. With the data that was obtained, the design of the exchanger is carried out. Likewise, the calculations of the pressure losses in the pipes and in the chimney are made.